The Effect of Principals’ Instructional Leadership, Work Culture, And Teachers’ Work Motivation on The Performance of Public Elementary School Teachers in Pulau Petak District - Sahbani Sahbani; Aslamiah Aslamiah; Metroyadi Metroyadi (Journal of General Education and Humanities, 2026)
Teacher performance is a key factor in determining the quality of education and is influenced by individual abilities, principal leadership, work culture, and teachers’ work motivation. Principals’ instructional leadership is crucial in guiding and facilitating teachers to conduct effective learning, while a positive work culture and high work motivation can sustainably improve teacher performance. This study analyzes the influence of principals’ instructional leadership and work culture on teacher performance, both directly and indirectly through work motivation, in public elementary schools in Pulau Petak District, Kapuas Regency. Using a quantitative survey method, the study involved 119 teachers selected from a population of 170 via proportional random sampling. Data were collected through validated and reliable Likert-scale questionnaires and analyzed using path and multiple regression analysis. Results indicate that principals’ instructional leadership, work culture, work motivation, and teacher performance are in the high to very high categories. Principals’ instructional leadership and work culture have significant direct effects on both work motivation and teacher performance, while work motivation also significantly affects teacher performance. Moreover, instructional leadership and work culture indirectly influence teacher performance through work motivation. These findings highlight that enhancing teacher performance requires strong instructional leadership, a supportive work culture, and high teacher motivation. The study suggests that school management should continuously strengthen leadership and cultivate a positive work environment to boost teachers’ motivation and performance, and it encourages further research on additional factors influencing teacher performance.